Natural Translating Locomotion Modulates Cortical Activity at Action Observation - Pozzo, Thierry; Inuggi, Alberto; Keuroghlanian, Alejo; Panzeri, Stefano; Saunier, Ghislain; Campus, Claudio (Frontiers in Systems Neuroscience, 2017)
The present study verified if the translational component of locomotion modulated cortical activity recorded at action observation. Previous studies focusing on visual processing of biological motion mainly presented point light walker that were fixed on a spot, thus removing the net translation toward a goal that yet remains a critical feature of locomotor behavior. We hypothesized that if biological motion recognition relies on the transformation of seeing in doing and its expected sensory consequences, a significant effect of translation compared to centered displays on sensorimotor cortical activity is expected. To this aim, we explored whether EEG activity in the theta (4-8 Hz), alpha (8-12 Hz), beta 1 (14-20 Hz) and beta 2 (20-32 Hz) frequency bands exhibited selectivity as participants viewed four types of stimuli: a centered walker, a centered scrambled, a translating walker and a translating scrambled. We found higher theta synchronizations for observed stimulus with familiar shape. Higher power decreases in the beta 1 and beta 2 bands, indicating a stronger motor resonance was elicited by translating compared to centered stimuli. Finally, beta bands modulation in Superior Parietal areas showed that the translational component of locomotion induced greater motor resonance than human shape. Using a classifier we found that Dorsal-Parietal and Inferior-Frontal ROIs, constituting the core of action-observation system, were the only areas capable to discriminate all the four conditions, as reflected by beta activities. Our findings suggest that the embodiment elicited by an observed scenario is strongly mediated by horizontal body displacement.